Viabilidade da adoção dos indicadores de sustentabilidade da diretriz GRI na estratégia de sustentabilidade organizacional em redes de micro e pequenas empresas - Vasconcelos, Patrício Henrique de (2012)
The world conjuncture convokes productive systems to act in a sustainable way. The sustainability indicators emerge as a fundamental strategic vector for businesses and organizations, regardless of the size or sector they operate. In this perspective, this study aimed to evaluate the feasibility of adopting sustainability indicators described in the GRI - G3 guidelines, in the organizational sustainability strategy in SMEs. The study was characterized as an applied research, as well as exploratory, descriptive, and survey. Through the application of questionnaires with the managers of enterprises affiliated to this productive cooperation network, it was possible to determine their stakeholders, identify the degree of relevance of the main sustainability indicators of the GRI (2007) in the environmental, economic and social categories, and evaluate the conditions of adoption feasibility by the affiliated enterprises. The main results indicate that the adoption of sustainability indicators listed in GRI guideline (2007) presents itself as a viable strategy for organizational sustainability of SMEs affiliated to the studied network.